2018
DOI: 10.1186/s40069-018-0268-1
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Responses of Prestressed Hybrid Wide Flange Composite Girders

Abstract: In this study, prestressed hybrid wide flange (PHWF) composite girders were proposed, and full-scale flexural tests were conducted to evaluate their structural performances. This new proposed girder system was developed and designed to effectively resist external loads considering the actual construction sequences. Two specimens with and without shear connectors were fabricated and tested to examine the effect of the shear connectors for achieving the fully-composite behaviors between a cast-in-place (CIP) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In this study, a layered analysis [17,18] shown in Figure 8a was performed to evaluate the flexural behavior of the JAS. Since no damage at the interface between the PC unit slab and cast-in-place concrete was observed in the CF specimen, the PC and the cast-in-place concrete were considered to be fully composite in the flexural analysis.…”
Section: Non-linear Flexural Analysismentioning
confidence: 99%
“…In this study, a layered analysis [17,18] shown in Figure 8a was performed to evaluate the flexural behavior of the JAS. Since no damage at the interface between the PC unit slab and cast-in-place concrete was observed in the CF specimen, the PC and the cast-in-place concrete were considered to be fully composite in the flexural analysis.…”
Section: Non-linear Flexural Analysismentioning
confidence: 99%
“…Composite structural systems are widely used in construction sites because they afford long spans and reduced floor heights. In this regard, steel-concrete composite members with structural performance improved by efficiently utilizing the advantages of concrete and steel [1][2][3][4][5][6][7], prestressed concrete members with flexural and shear performance improved by introducing prestress into concrete with low tensile strength [8][9][10], and composite members applied with fibers and high-performance materials [11][12][13][14][15][16][17][18][19] have been developed hitherto.…”
Section: Introductionmentioning
confidence: 99%